Padanan Aspek Pragmatik Jugendsprache dalam Film Serial Netflix Berbahasa Jerman: HTSDO(F) - Lelyansari, Edwina; Rosyidah (Nexus Publishing, 2024)
This study aims to identify the basic aspect in using Jugendsprache and to describe the pragmatic equivalence of the utterances in the German-language film series produced by Netflix, “How to Sell Drugs Online (fast)”. This is descriptive qualitative research with conventional content analysis method. The research data were derived by listening, reading, and noting techniques. The results of the study show that the use of Jugendsprache in the film series ist mostly based on two aspects, namely the credibility aspect and the affective-emotional aspect. Both aspects are related to the nature of teenagers whos tend to interact with their fellows. In addition, the results also showed that the equivalence of Jugendsprache utterances has been given an appropriate equivalent by considering pragmatic aspect to coney the intended meaning by the speaker.